Strategic sourcing in the public sector - Grilli, Barbara A.; Webb, Theresa G. (Routledge, 2023)
Effective sourcing in the public sector is a collaborative and strategic process that does not end when the contract or purchase order is executed. As an ongoing process of improvement, strategic sourcing requires regular appraisals of procurement activities to ensure they continue to support the goals of the entity. Strategic Sourcing in the Public Sector explains the theory behind sourcing. Why does sourcing need to be strategic, and what are the stakeholders' roles in the process? Written to complement the Institute of Public Procurement's (NIGP) Sourcing and Solicitation curriculum, this book explores the impetus or the 'why' behind the sourcing process as well as the 'how.'